The Influence of Combining Ideological and Political Courses with Physical Education on the Psychological Resilience of College Students - Boluo Shi; Kun Hou, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to understand the impact of sports on the psychological resilience of ordinary university students, the author proposes a study based on the combination of ideological and political courses with sports on the psychological resilience of ordinary university students.The author takes the psychological resilience characteristics and influencing factors of physical education college students in a certain province as the research object. By conducting interviews with experts and reviewing information and designing a survey questionnaire on the influencing factors of psychological resilience. The influencing factor questionnaire consists of 28 questions, with a 5-level scoring system, the score ranges from "very non-compliant" to "very compliant" with a score of "1-5", representing "very non-compliant", "non-compliant", "generally compliant", "quite compliant", and "very compliant". A total of 260 questionnaires were distributed, and 240 valid questionnaires were collected, with a recovery effectiveness rate of 91%. The research results indicate that the psychological resilience level of males is higher than that of females in this group. The level of psychological resilience is manifested as "freshman>sophomore>junior", and gradually decreases with the increase of grade.Psychological resilience, as a protective factor for individuals facing stress, can enable them to demonstrate good adaptability after encountering setbacks. Psychological resilience has a promoting effect on the improvement of an individual's mental health level, while also alleviating adverse psychological conditions.